2016
DOI: 10.1093/europace/euw153
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine vs. placebo for the treatment of recurrent vasovagal syncope with anxiety sensitivity

Abstract: Sensitivity to anxiety is a common personality trait in recurrent VVS. Fluoxetine is superior to placebo against syncope in these patients. This drug may be a first-line pharmacological treatment for this difficult-to-treat group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Individuals with high levels of anxiety sensitivity have a tendency toward showing exaggerated and prolonged reactions to anxiety‐provoking stimuli. A recent study examined whether fluoxetine, a serotonin‐reuptake inhibitor (SSRI) and effective therapy for anxiety and panic disorders, was able to prevent VVS in patients with elevated anxiety sensitivity (60/106 patients assessed) . The study found that patients receiving fluoxetine reported a significant decrease in the incidence of syncope and presyncope during follow‐up compared to patients receiving placebo (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with high levels of anxiety sensitivity have a tendency toward showing exaggerated and prolonged reactions to anxiety‐provoking stimuli. A recent study examined whether fluoxetine, a serotonin‐reuptake inhibitor (SSRI) and effective therapy for anxiety and panic disorders, was able to prevent VVS in patients with elevated anxiety sensitivity (60/106 patients assessed) . The study found that patients receiving fluoxetine reported a significant decrease in the incidence of syncope and presyncope during follow‐up compared to patients receiving placebo (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study examined whether fluoxetine, a serotonin-reuptake inhibitor (SSRI) and effective therapy for anxiety and panic disorders, was able to prevent VVS in patients with elevated anxiety sensitivity (60/106 patients assessed). 21 The study found that patients receiving fluoxetine reported a significant decrease in the incidence of syncope and presyncope during follow-up compared to patients receiving placebo (P < 0.05). SSRIs have also been suggested in the treatment of VVS due to the effect of serotonin on the modulation of heart rate and blood pressure, although results from previous studies have been mixed.…”
Section: Vvs and Psychological Distressmentioning
confidence: 91%
“…Also, SSRIs had a positive effect on the refractory recurrent syncope episodes [12,45]. A recent study demonstrated that fluoxetine could be considered as the first-line treatment in VVS patients with recurrent syncope episodes and psychogenic disorders [46]. Similarly, Kadri et al observed a significant improvement with citalopram treatment in syncope patients when the primary endpoint was considered as a well-being score (WS) [47].…”
Section: -Tse Was Correlated Significantly and Positively Withmentioning
confidence: 99%
“…The study by Flint et al found a correlation between psychosocial impairment and response to treatment [14], which supports the recommendation that patients with VVS, who presents with psychosocial impairment should undergo a psychiatric evaluation by a therapist, especially in the light of other evidence that indicated the usefulness of psychotherapy and antidepressants in the treatment of refractory VVS [15][16][17][18][19]. This study was limited by the use of self-report measures for the psychosocial evaluation, and it didn't control for other co-morbidities that can affect the psychiatric condition of the patients.…”
Section: The Relationship Between Vvs and Psychological Distressmentioning
confidence: 77%